Maternal and Perinatal Outcomes for Women With Body Mass Index ≥50 kg/m2 in a Non-tertiary Hospital Setting. Issue 2 (24th June 2021) - Pratt, A.; Howat, P.; Hui, L.
Abstract : ( Aust N Z J Obstet Gynaecol . 2020;60:361–368) It is well known that maternal obesity increases the risk of several obstetric complications and interventions. However, data is limited regarding maternal prevalence and obstetric outcomes for obese Australian women, particularly for those with BMI ≥50 kg/m 2 . This study aimed to assess the prevalence of women with BMI ≥50 kg/m 2 in a non-tertiary setting and to analyze outcomes for pregnant women based on BMI, with an emphasis on women with BMI ≥50 kg/m 2 .